THE INFLUENCE OF HARDINESS AND SELF EFFICACY IN OVERCOMING ACADEMIC BURNOUT ON STUDENTS AT ISLAMIC BOARDING SCHOOLS - Fauziah, Ely; Rusyid Affandi, Ghozali (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to examine the influence of hardiness and self-efficacy on academic burnout among students in Islamic boarding schools. Method: The research involved 140 male and female students in grades 7–9 who live and study in Islamic boarding schools, selected using non-probability accidental sampling from a total population of 180. Data were collected through offline and online questionnaires utilizing the Dispositional Resilience Scale (DRS-15), the General Self-Efficacy Scale, and the School Burnout Inventory (SBI). Results: The results of multiple linear regression analysis indicate that hardiness and self-efficacy together significantly influence academic burnout, with an F-value of 135.865 and p < 0.001. The coefficient of determination (R² = 0.665) suggests that 66.5% of the variance in academic burnout can be explained by the combined influence of these two variables, while the remaining 33.5% is attributed to other factors. Novelty: This study contributes to the literature by highlighting the predictive role of psychological resilience and belief in one's capabilities in reducing academic burnout in a boarding school context, offering insights for the development of targeted psychological interventions within religious educational settings.